Tuning direct-written terahertz metadevices with organic mixed ion-electron conductors - Cristiano Bortolotti; Federico Grandi; Matteo Butti; Lorenzo Gatto; Francesco Modena; Christina Kousseff; Iain McCulloch; Caterina Vozzi; Mario Caironi; Eugenio Cinquanta; Giorgio Ernesto Bonacchini (Nature Communications)
Abstract In the past decade, organic mixed ion-electron conductors have been successfully adopted in innovative bioelectronic, neuromorphic, and electro-optical technologies, as well as in multiple energy harvesting and printed electronics applications. However, despite the intense research efforts devoted to these materials, organic mixed conductors have not yet found application in electronic/photonic devices operating in key regions of the electromagnetic spectrum, such as the microwave (>5 GHz) and terahertz (0.1-10 THz) ranges. A possible reason for this technological gap is the widespread notion that organic electronic materials are unsuitable for high-frequency applications. In this work, we demonstrate for the first time the utility of high-performance polymer mixed conductors as electro-active tuning layers in reconfigurable terahertz metasurfaces, achieving modulation performances comparable with state-of-the-art inorganic and 2D semiconductors. Through time-domain terahertz spectroscopy, we show that the large conductivity modulations of these polymers, until now probed only at very low frequencies, are effectively preserved in the terahertz range, leading to optimal metadevice reconfigurability. Finally, we leverage the unique processability of organic materials to develop fully direct-written electrically tuneable metasurfaces onto both rigid and flexible substrates, opening new opportunities for the mass-scale realization of flexible and light-weight terahertz optics with unique mechanical characteristics and environmental footprint.